2013
DOI: 10.3892/mco.2013.66
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of palliative prognostic score in the treatment of patients with non-resectable gastric cancer

Abstract: Abstract. The aim of this study was to evaluate the clinical usefulness of the palliative prognostic (PaP) score in patients with non-resectable advanced gastric cancer. The PaP score was calculated prior to each course of chemotherapy in 44 consecutive patients with non-resectable advanced gastric cancer between 2003 and 2010 at the Tottori University Hospital, Yonago, Japan. The prognosis was evaluated according to the PaP score and the different chemotherapeutic agents. The median survival time (MST) was 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Previously, we found that fucoidan could reduce the toxicities of chemotherapy drugs in patients with colorectal cancer [3]. Thus, in the present study, we analyzed whether fucoidan could protect patients from the toxicities of S-1 plus cisplatin in patients with unresectable gastric cancer and whether this resulted in prolonging the patients' survival.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previously, we found that fucoidan could reduce the toxicities of chemotherapy drugs in patients with colorectal cancer [3]. Thus, in the present study, we analyzed whether fucoidan could protect patients from the toxicities of S-1 plus cisplatin in patients with unresectable gastric cancer and whether this resulted in prolonging the patients' survival.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, S-1 plus cisplatin versus S-1 alone for first-line treatment of advanced gastric cancer (SPIRITS) trial identified the S-1 plus cisplatin regimen, which comprises S-1 at a dose of 40 -60 mg/m 2 , in a 5-week cycle (3 weeks on and 2 weeks off), and cisplatin at a dose of 60 mg/m 2 cisplatin on day 8, as a standard first-line treatment for unresectable gastric cancer in Japan [2]. Unfortunately, the severe side effects of this treatment mean it is difficult for most patients to continue the S-1 plus cisplatin regimen [3], and many patients suffer from reduced QOL [4]. Thus, it is clinically important to reduce the toxicity of the chemotherapy regimen so it can be more effective for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Another Palliative prognostic model, the Palliative prognostic score was used to predict the survival of advanced cancer patients receiving systemic anticancer therapy. [ 14 15 ] The Palliative prognostic score ranges from 0 to 17.5 and is based on six items, dyspnea, anorexia, Karnofsky performance status, clinician prediction of survival, total white blood cell count and lymphocyte percentage. [ 16 ] In one study, a heterogenous population of 173 patients with pretreated advanced solid tumors were grouped according to the Palliative prognostic score before starting further palliative chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The median survival of three risk groups was 17, 7, and < 1 w, respectively. A retrospective study of Ikeguchi et al was unique because it revealed that patients with non-resectable gastric cancer who were classiied into the low-risk group by the PaP score received a more toxic irst-line regimen, whereas patients with a high-risk score received a less toxic regimen [57]. Ikeguchi et al concluded that the PaP score may be a promising tool for selecting a chemotherapy regimen for patients with non-resectable gastric cancer.…”
Section: Palliative Prognostic (Pap) Scorementioning
confidence: 99%
“…In the oncology seting, the validation studies were performed in Australia, Italy, and Japan [56][57][58][59]. Initially, a validation study of the oncology seting was reported by Glare et al in 2004, recruiting 100 patients receiving medical or radiation oncology care [56].…”
Section: Palliative Prognostic (Pap) Scorementioning
confidence: 99%